2006
DOI: 10.1590/s0101-81752006000400027
|View full text |Cite
|
Sign up to set email alerts
|

Kroyeria brasiliense sp. nov. (Copepoda, Kroyeriidae)a gill parasite of the shark, Galeorhinus vitaminicus de Buen, in Rio Grande do Sul State, Brazil

Abstract: Kroyeria brasiliense sp. nov. from the shark, Galeorhinus vitaminicus de Buen, 1950, from Rio Grande do Sul, State, Brazil, is described on the basis of 14 adult females. The new species is superficially similar to Kroyeria deetsi Dippenaar, Benz & Olivier, 2000, but differs from it in the following characters. The maxillipeds of the new species are large and project well beyond the lateral margins of the cephalothorax. Those of K. deetsi are much smaller. The third endopodal segments of K. deetsi are twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Kroyeria brasiliense Thatcher & Pereira Jr. Galeorhinus galeus, gills, marine, Rio Grande do Sul (Thatcher & Pereira Jr. 2006).…”
Section: Family Kroyeriidae Kabatamentioning
confidence: 99%
“…Kroyeria brasiliense Thatcher & Pereira Jr. Galeorhinus galeus, gills, marine, Rio Grande do Sul (Thatcher & Pereira Jr. 2006).…”
Section: Family Kroyeriidae Kabatamentioning
confidence: 99%
“…1 to 6) and the line diagrams (Plate-2; Figs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Deets, 1994 Similar in appearance to K. cresseyi, K. lineata, K. rhophemophaga and K. triakos in that the antenna has a claw with only two slender setae.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed review of Kroyeria species, their distinctive features, reported hosts and their geographical locations is described [13,16,10,11] (Table 1). The species described in the present paper was identified as Kroyeria minuta because it showed the distinctiveness described by Pillai (1968) in the original description.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation